2019
DOI: 10.1007/s00018-019-03185-3
|View full text |Cite
|
Sign up to set email alerts
|

Isorhapontigenin (ISO) inhibits stem cell-like properties and invasion of bladder cancer cell by attenuating CD44 expression

Abstract: Cancer stem cells (CSC) is highly associated with poor prognosis in cancer patients. Our previous studies report that isorhapontigenin (ISO) downregulates SOX2-mediated cyclin D1 induction and stem-like cell properties in glioma stem-like cells. The present study revealed that ISO could inhibit stem cell-like phenotypes and invasivity of human bladder cancer (BC) by specific attenuation of expression of CD44 but not SOX-2, at both the protein transcription and degradation levels. On the one hand, ISO inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 54 publications
(64 reference statements)
1
24
0
Order By: Relevance
“…Furthermore, ISO causes the induction of miR-4295, which inhibited the usp28 translation and expression in bladder cancer cells [62]. Interestingly, ISO also exerts an antiproliferative effect on both estrogen-dependent human cancer cell lines MCF-7 (the IC 50 value of 34.16 µM) and T47D, and triple-negative breast cancer cell line MDA-MB-231 by induction of oxidative stress and cell cycle arrest [63].…”
Section: Isorhapontigenin-successor Of Resveratrolmentioning
confidence: 98%
See 2 more Smart Citations
“…Furthermore, ISO causes the induction of miR-4295, which inhibited the usp28 translation and expression in bladder cancer cells [62]. Interestingly, ISO also exerts an antiproliferative effect on both estrogen-dependent human cancer cell lines MCF-7 (the IC 50 value of 34.16 µM) and T47D, and triple-negative breast cancer cell line MDA-MB-231 by induction of oxidative stress and cell cycle arrest [63].…”
Section: Isorhapontigenin-successor Of Resveratrolmentioning
confidence: 98%
“…These authors also demonstrated using C57BL/6J male mice that ISO (150 mg/kg/day in drinking water for 20 weeks) might inhibit mouse-invasive cancer growth induced by N-butyl-N-(4-hydroxybutyl) nitrosamine (BBN) (0.05% in drinking water for 20 weeks) [ 61 ]. Luo et al proved that ISO at a concentration of 20 μM used in T24T cell culture, could affect CD44 protein and cd44 mRNA expression through decreases in Sp1 direct binding, which inhibited stem cell-like phenotypes and invasiveness of the tumour [ 62 ]. It has also been observed that protein expression involved in the DNA damage pathway, ubiquitin-specific peptidase 28 (USP28) was reduced; as a result, CD44 protein stability was decreased [ 62 ].…”
Section: From Hydroxyl To Methoxy-stilbene Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…RBE cells were transiently transfected with CDR1as-OV, CDR1as-sh2, miR-641 mimics, or controls in the presence of 20 g/ml actinomycin D (Act D) (catalog number HY-17559; MCE, Monmouth Junction, NJ) for the indicated times (0, 4, 8, and 24 h). Act D, an inhibitor of DNA-dependent RNA synthesis, was used to assess the stability and degradation of miRNA and mRNA (51)(52)(53). The remaining levels of miRNA and mRNA were related to RNA degradation for the indicated times.…”
Section: Fig 10mentioning
confidence: 99%
“…At present, research have reported that there is a rare subpopulation of cells in primary tumors called cancer stem cell‐like cells (CSLCs). Compared with normal cells, which are more aggressive and can cause distant metastasis of tumors . Epithelial cell adhesion factor (EpCAM, CD326) has been shown to play a role in many tumors, including cell signal transduction, associating with tumor cell proliferation, migration, and invasion, promoting cancer progression, which can be used as prognostic markers of cancers .…”
Section: Introductionmentioning
confidence: 99%